Holocene environmental changes and human activity at the Jijitan site in the Nihewan Basin, China. (July 2018) - Lu, Jingyao; Xu, Qinghai; Liu, Yao; Hu, Ya'nan; Li, Manyue; Zhang, Shengrui
Knowledge of the relationship between human activities and environmental changes during the Holocene is important for understanding the survival and development of prehistoric humans. Using AMS 14 C dating and pollen and charcoal analysis, we reconstructed the history of environmental changes and human activity during the Holocene at the Jijitan site in the Nihewan Basin. During 13, 000–7500 cal. yr BP, the East Asian Summer Monsoon (EASM) gradually intensified and precipitation increased, the vegetation changed from temperate grassland to wooded grassland and human activity remained at a low intensity. During 7500–5500 cal. yr BP, the EASM reached peak level, and the climate was warm and humid interval, and human activity intensified substantially. Within this interval, from 6600 to 6000 cal. yr BP, the forests were burned to increase the area of farmland. After 5500 cal. yr BP, the forest cover continued to gradually decrease due to the combined influences of the weakening EASM and increasing human activity. Comparison with regional climate records shows that the optimum period of forest development in northern China was approximately 8000–5000 cal. yr BP, indicating that the EASM reached a peak level in the mid-Holocene, which we suggest may have been due to the reduced influence of the high northern-latitude ice sheets and rising global sea level, rather than in the early Holocene.